PENGARUH SEGMENTASI, TARGETING DAN POSITIONING (STP) TERHADAP KEPUTUSAN PEMBELIAN PADA KM WARMINDO - Kasim, Muhammad Farhan Fauzan; Samdin, Samdin; Hamid, Wahyuniati; Hartini, Hartini; Sukotjo, Endro (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims: (1) To determine the effect of segmentation, targeting and positioning (STP) on purchasing decisions at KM warmindo. (2) To determine the effect of segmentation on purchasing decisions at KM warmindo. (3) To determine the effect of targeting on purchasing decisions at KM warmindo. (4) To determine the effect of positioning on purchasing decisions at KM warmindo. The population in this study is all customers of KM Warmindo whose number is unknown (unknown population). The sample in this study amounted to 96 respondents with the determination of the sample referring to the statement of Hair et al. The data collection method in this study used multiple linear regression analysis. The research results show that: (1) Segmentation, targeting and positioning (STP) have a positive and significant effect on purchasing decisions. (2) Segmentation has a positive and significant effect on purchasing decisions. (3) Targeting has a positive and significant effect on purchasing decisions. (4) Positioning has a positive and significant effect on purchasing decisions.